Photochemical and electrochemical properties of tetranuclear Ru (II) complexes - Tripathi, P N; Verma, Smriti; Singh, R P (Recent Research in Science and Technology, 2012)
The luminescent and redox active multinuclear Ru (II) Complex containing both electron poor (2,3-bis (2-pyridyl) pyrazine, 2,3-dpp) and electron rich (3,5-bis (pyridyn-2yl)-1,2,4-¬triazole, Hppt) polypyridine bridging ligands has been synthesized. The novel complex is [ (phen)2 Ru (µ-bpt)Ru{(µ-2,3-dpp) Ru(Phen)2}2]7+ (1:Phen-=1,10-Phenanthroline) Its absorption spectrum, luminescence properties, and redox behavior have been studied and compared with the properties of parent complexes [Ru {(µ-2,3-dpp) Ru (Phen)2}3]8+ (2) and [(Phen)2 Ru (µ-bpt) Ru (Phen)2]3+ (3). The absorption spectrum of 1 is dominated by ligand centered bands in the U.V. region and by metal to ligand CT bands in the visible region. Excited states and oxidation and reduction processes are localized in specific sites of the multicomponent structure. However, perturbations of each component on the redox and excited state properties, as well as electronic interactions between the chromospheres can be observed. Intercomponent energy transfer from the upper lying (µ-bpt) (Phen) Ru ï§Phen CT ¬excited state of the Ru (Phen)2 (µ-bpt)+ component to the lower lying (Phen)2 RUï§ µ 2,3-dpp CT excited - state of the Ru (Phen)2 (µ-2,3-dpp)2+ subunit(s) is efficient in fluid solution at room . And the process is not observed in a rigid matrix at 77 K. A two step energy transfer mechanism is proposed to explain the photophysical properties of the new complex.